Current situation of violence against women: evolution and impact in Peru - Roda G., Julinho Bryams (2022)
Objective: To carry out a systematic review of various publications on the current situation of violence against women, as well as its evolution and impact in Peru. Methods: It was carried out through the electronic search of various scientific articles related to the subject. The search sources were PubMed, Scielo, and Google Scholar. The keywords were: «violence against women», «impact», «self-esteem» and «Peru». Results: Of the 99 articles found, 69 were discarded because they did not meet the inclusion criteria, leaving 30 articles for this review. Conclusion: Violence is present in most moments of our lives, manifesting itself in different ways, among them is violence against women, which is exercised in different ways, either by physical abuse or verbal abuse.